Efficient Photocatalytic Oxidation of Aromatic Alcohols over Thiophene‐based Covalent Triazine Frameworks with A Narrow Band Gap. Issue 45 (2nd December 2020) - Liao, Longfei; Ditz, Daniel; Zeng, Feng; Alves Favaro, Marcelo; Iemhoff, Andree; Gupta, Kavita; Hartmann, Heinrich; Szczuka, Conrad; Jakes, Peter; Hausoul, Peter J. C.; Artz, Jens; Palkovits, Regina
Abstract: Photocatalytic selective oxidation of aromatic alcohols by covalent organic frameworks (COFs) is a sustainable strategy to replace present metal‐based heterogeneous catalytic oxidation systems. Covalent triazine‐based frameworks (CTFs), a subgroup of COFs, possess promising properties as efficient catalysts for photocatalytic oxidation. Sulfur‐containing metal‐free CTFs exhibit a good performance in photocatalysis due to their narrowed band gap, and the fast generated photoelectrons/holes separation and transfer. Here, we report the synthesis of thiophene‐based CTFs under mild conditions for photocatalytic oxidation of aromatic alcohols to the corresponding benzaldehydes using pure oxygen as the oxidant. Full conversion and a selectivity as high as 90 % to benzaldehyde were obtained paving the way for a potential application of these metal‐free photocatalysts in fine chemicals synthesis. Abstract : Sulfur‐containing metal‐free photocatalysts exhibit a good performance in photocatalysis due to their narrowed band gap, and the fast generated photoelectrons/holes separation and transfer. Here, we report the synthesis of thiophene‐based CTFs under mild conditions for photocatalytic oxidation of aromatic alcohols to the corresponding benzaldehydes using pure oxygen as the oxidant. Full conversion and a selectivity as high as 90 % to benzaldehyde were obtained paving the way for a potential application of these metal‐free photocatalysts in fine chemicals synthesis.